Improved Binary Bat Algorithm for Optimally Placing Multiple DGs in RDN - Saxena, N.; Pandit, M.; Srivastava, L. (Proceedings of ... IEEE Power India International Conference (Online), 2022)
Identification of optimal location for placing distributed generators for the mitigated power losses and upgraded voltage profile in radial distribution network is presented in this article. Load flow solution is obtained using Backward-Forward Sweep method. Improved Binary Bat algorithm, as optimization technique, is used to evaluate the possible best location and magnitude of dispersed generators. Analysis is done by simulating over IEEE-33 and IEEE-69 bus system. Results signifies the loss reduction with voltage profile improvement.